Martin Heidegger and Zhuangzi’s concept of death - Cheong, Terence Ming Wei (2019)
Martin Heidegger is one of the few Western philosophers to depict death as a contribution to the perfection of being. He came up with the notion of Dasein not perishing but experiencing its own demise with death standing before humanity as something to be anticipated. When man leads an authentic attitude in being-towards-death, he is anticipating the possibility of emerging free for his death. Heidegger holds the position that authentic living indicates that death should not be something to be feared upon, rather, one can live a fuller life realising that one's time is limited and death can happen unexpectedly or far sooner than expected. For Heidegger, death is inevitable and non-relational.